The greatest fight of our generation : Louis vs. Schmeling - Erenberg, Lewis A., 1944- (Oxford University Press, 2006)
Lewis A. Erenberg describes a boxing match that transcended the sport to become an iconic event, a symbol of political tensions around the globe. On 22 June 1938, Joe Louis, who had been defeated in 12 rounds by Max Schmeling, won the rematch in just two minutes.